The right to coose or the rght to kill: The divisive issue of abortion in American past and present - Krajovanová, Jitka (2006)
This B.A. thesis deals with abortion as a social problem in the United States of America. The issue is inquired into from a variety points of view. Topics like religion, public opinion (including public opinion polls, the role of the media and politics), pro- and anti-abortion organizations and anti-abortion extremism are taken into consideration and the issue is examinded in a wider social context. A substantial part of the thesis is devoted to the current issues in the United States: the role of the Supreme Court, emergency contraception, partial-birth abortion and many others